2018
DOI: 10.1007/978-3-319-98654-8_21
|View full text |Cite
|
Sign up to set email alerts
|

A General Approach to State Complexity of Operations: Formalization and Limitations

Abstract: The state complexity of the result of a regular operation is often positively correlated with the number of distinct transformations induced by letters in the minimal deterministic finite automaton of the input languages. That is, more transformations in the inputs means higher state complexity in the output. When this correlation holds, the state complexity of a unary operation can be maximized using languages in which there is one letter corresponding to each possible transformation; for operations of higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…for every regular language L and every 1-uniform morphism φ, ⊗(φ −1 (L)) = φ −1 (⊗(L)). For example, it is proven in [8] that the Kleene star and the reverse are 1-uniform. Suppose now that ⊗ is a unary 1-uniform operation.…”
Section: Modifiersmentioning
confidence: 99%
See 1 more Smart Citation
“…for every regular language L and every 1-uniform morphism φ, ⊗(φ −1 (L)) = φ −1 (⊗(L)). For example, it is proven in [8] that the Kleene star and the reverse are 1-uniform. Suppose now that ⊗ is a unary 1-uniform operation.…”
Section: Modifiersmentioning
confidence: 99%
“…Witnesses with small alphabets are indeed favoured in this area of research when they can be found, as evidenced by several studies ( [5,6]). This approach has been described independently by Caron et al in [3] as the monster approach and by Davies in [8] as the OLPA (One Letter Per Action) approach but was implicitly present in older papers like [2,10].…”
Section: Introductionmentioning
confidence: 99%
“…Next, to reach any valid state in the most easier way, it is relevant to consider automata K and L having a maximum of transitions. This is the idea of monsters detailed in [4,6] and formalized in the next section. Brzozowski et al implicitly use this notion to prove the result for any n when m ≤ 5.…”
Section: The Shuffle Productmentioning
confidence: 99%
“…In some cases, the classical method has to be enhanced by an algebraic approach consisting in building a witness for a certain class of rational operations by searching in a set of automata with as many transition functions as possible. This method has the advantage of being applied to a large class of operations and has been described independently by Caron et al in [4] as the monster approach and by Davies in [6] as the OLPA approach but was implicitly present in older papers like [2], [7].…”
Section: Introductionmentioning
confidence: 99%
“…The authors learned that Sylvie Davies has independently and in the same time obtained some of the results presented in this paper. Her work can be found in [7].…”
mentioning
confidence: 99%